Towards Obtaining High Quality Sentence-Aligned English-Croatian Parallel Corpus - Brkić, Marija; Matetić, Maja; Seljan, Sanja (2011)
This paper presents the acquisition of parallel bilingual corpus and all the steps involved in the process of unsupervised sentence alignment, such as tokenization, lowercasing, etc. The problem of sentence alignment is not trivial because translators do not necessarily translate one sentence in the source language into one sentence in the target language. Three different unsupervised and language independent approaches to sentence alignment are presented and implementations of these approaches through three different freely available tools are tested. A gold standard for English-Croatian automatic sentence alignment evaluation is created. Finally, a detailed analysis of the acquired corpus is given.
Projekt MZOS
ENG